PENGARUH STRESS KERJA TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Bagian Account Officer BPR Cirebon) - Gunawan, Asep; Ulfa’i, Ulia (VALUE, 2018)
This study aims to obtain empirical evidence whether or not the influence of job stress on turnover intention with job satisfaction as intervening variable. This research uses data questionnaire and data processing assisted by SPSS 20. The sample of this research is 38 employees of BPR Account Officer in Cirebon. The results of this study indicate that the job stress has a positive effect on turnover intention through job satisfaction as intervening variable, but its value is smaller than the effect of job stress on direct turnover intention. It also shows that job satisfaction can decrease the turnover intention level of employees of BPR Account Officer in Cirebon, caused by job stress. Keywords: job stress, turnover intention, job satisfaction